Получение молибдат содержащего NI-TI слоистого двойного гидроксида одностадийным обратным синтезом и изучение его характеристик - Соловов, Виталий Андреевич; Николенко, Николай Васильевич; Коваленко, Вадим Леонидович; Коток, Валерий Анатольевич; Бурков, Андрей Алексеевич (НТУ "ХПИ", 2016)
Образец молибдат-содержащий Ni-Ti слоистый двойной гидроксид был получен одностадийным обратным синтезом: постепенным введением раствора солей никеля и титана в раствор щелочи с добавкой гептамолибдата аммония при постоянно перемешивании и комнатной температуре. Структура образца как слоистого двойного гидроксида подтверждена результатами ИК-спектроскопии, РФА и дериватографии. По данным ИК-спектроскопиии было показано наличие в межслоевом пространстве СДГ гептамолибдат- анионов. РСМА установлено следующее соотношение металлов в синтезированном СДГ Ni:Ti:Мо=1:0,19:0,22.

The molybdate intercalated layered double hydroxides can be potentially applied as catalysts for organic synthesis and oxidation. According to literature they are most commonly prepared using multi-stage methods such as anion-exchange and rehydration of calcinated LDH precursor. Aim of the work was to study a possibility of one-stage synthesis of molybdate-intercalated Ni-Ti LDH. To achieve the set-out aim, a sample of molybdate-intercalated Ni-Ti LDH has been prepared using one-step coprecipitation at high supersaturation at room temperature synthesis method: drop-wise introduction of nickel and titanium salts solution into solution of sodium hydroxide and ammonium heptamolybdate. The prepared sample was characterized by SEM, XRD, FTIR, TG-DTA and EDX. Hydrotalcite-like structure has been confirmed by results of XRD, FTIR and TG. The results of SEM have showed that sample morphology is constituted by spherical agglomerates. According to XRD results the prepared sample has rather low crystalinity. The results of TG-DTA showed that thermal decomposition of the sample occurs into two stages: 1) 90-180oC accompanied by an endothermic event and associated with loss of adsorbed and interlayer water; 2) 280-340oC accompanied by an endothermic event and associated with dehydroxilation brucite-like layered, transformation of LDH into LDO and, possibly, transformations in Ni-Ti-Mo-O system. Results of FTIR have confirmed successive intercalation of molybdate anion into interlayer space of Ni-Ti LDH. The results of FTIR also indicate presence of polymobdate forms. The results of EDX analysis showed molar ratio of Ni:Ti:Мо=1:0,19:0,22. The acquired results show the possibility of one-stage synthesis of molybdate intercalated Ni-Ti LDH.
Syntheis of molybdate-intercalated NI-TI layered double hydroxide by coprecipitation at high supersatureation and characterization
Keywords: гептаамолибдат аммония; ИК-спектроскопия; дериватография; РФА; гексамолибдат-иона; molybdate-intercalated Ni-Ti LDH; heptamolybdate; one-stage synthesis